NUEVAS RANAS DEL GÉNERO ELEUTHERODACTYLUS (FAMILIA LEPTODACTYLIDAE) DE LA REGIÓN DE SAN ANTONIO DE LA CORDILLERA OCCIDENTAL DE COLOMBIANA - Lynch, John D. (Revista de la Academia Colombiana de Ciencias Exactas, Físicas y Naturales, 1996)
Seventeen species of Eleutherodactylus are known from a cloud forest locality (finca San Pedro) at 1700-2000 m in Municipio Dagua, Depto. Valle del Cauca, Colombia, including two poorly-known species, E. calcaratus and E. palmeri. These 17 species make up the eleutherodactyline fauna found at severa! sites within the forests of San Antonio. Eleutherodactylus calcaratus and E. palmeri are redescribed based on fresh material and four species, previously unknown, are named from these forests.